KINETIC CHARACTERISTICS OF HETEROGENEOUS DISSOCIATION REACTION OF CODEINE MOLECULES ON OXIDIZED TUNGSTEN SURFACE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The dissociative surface ionization (SI) of codeine molecules was investigated using nonstationary SI methods under identical experimental conditions with a high-vacuum mass spectrometric setup equipped with a liquid-nitrogen-cooled “black chamber.” For pre-adsorbed morphine molecules, the dissociation rate constants and the activation energy of the bond-breaking reaction accompanied by the formation of ionizable radicals through surface ionization were determined. During the adsorption of codeine molecules, the rate constants , the activation energies of thermodesorption , and the pre-exponential factors in the continuity equation for radicals with were obtained. Additionally, thermal desorption surface ionization spectroscopy of codeine molecules was performed in an air atmosphere, and the activation energy of thermal desorption of a codeine molecule in air was determined from the thermal desorption spectra.
Keywords: nonstationary surface ionization, modulation method, voltage modulation method, codeine, adsorption, radicals, rate constants and activation energies of thermal desorption